The frequency of distribution of the genotypes of the IL4 polymorphism (rs 2243250) in psoriasis and psoriatic arthritis - A. A. Barilo; M. V. Smolnikova; S. V. Smirnova (Вавиловский журнал генетики и селекции)
Psoriasis (PS) and psoriatic arthritis (PsA) are multifactorial diseases determined by the result of complex combined interaction of genetic and environmental factors. The study of genetic polymorphism of PS and PsA will allow identification of common diagnostic criteria for the progression of pathology. The aim was to analyze the frequency of distribution of genotypes of the promoter region of the C-590T (rs2243250) gene IL4 in patients with psoriasis and psoriatic. The study included patients with psoriasis (n = 49) and psoriatic arthritis (n = 48), which, taking into account the carriage of certain genotypes, are divided into groups: 1, PS, carriers of the C/С genotype (n = 31); 2, PS, carriers of the C/T and T/T genotype (n = 18); 3, PsA, carriers of the C/С genotype (n = 30); and 4, PsA, carriers of the C/T and T/T genotype (n = 18). DNA extraction from whole venous blood was performed using a standard kit with a sorbent. Genotyping allelic variants was carried out by the method of restriction analysis of amplification products (RFLP-analysis) of specific regions of the genome. In PS carriers of the C/С IL4 (rs2243250), the value of the PASI index is statistically significantly lower relative to the carriers of the C/T and T/T genotypes. A possible association of the carriage of the C/T and T/T genotypes in PsA with nail psoriasis was noted in comparison with the C/C genotype. When studying intergroup differences, it was determined that the carriage of the C/C genotype in PsA can influence the clinical course of the psoriatic process with frequent exacerbations and involvement of more than 30 % of the hairy part in the pathological process. The carriage of the C/T and T/T genotypes in PsA may be associated with the Koebner phenomenon and the metabolic disorders in comparison with PS. Differences in the carriage of the C/C genotypes relative to C/T and T/T IL4 (rs2243250) in psoriasis and psoriatic arthritis were determined. Given the extremely low number of patient groups, the results should be considered as preliminary and require further testing on much larger samples.